Child well-being in Vietnam: The roles of household welfare and early childbearing - Hoang, Hue Thi; Ngo, Phuong Thi Xuan; Nguyen, Lan Thi; Le, Yen Thi Bao; Tran, Chi Khanh; Le, Phung Trung (Journal of Social Economics Research, 2023)
Children are important resources for nations' long-term and sustainable development; therefore, they have the right to have their well-being ensured from birth. Although multidimensional methods for researching child well-being in Vietnam have made some progress, most studies still focus on single aspects of child well-being. This paper analyzes the correlations between household welfare (measured by the asset index - an effective alternative tool to income and expenditure), early childbearing, and child well-being (in six constitutive dimensions) to provide a broad picture of the above relationships in the Vietnamese context. Using secondary data from the Vietnam Sustainable Development Goal Indicators for Children and Women (SDGCW) survey by the General Statistics Office (GSO) of Vietnam and the United Nations International Children's Emergency Fund (UNICEF) in the period 2020–2021, and applying Tobit and OLS regression models, the research results show that a high level of household welfare not only directly increases child well-being but also has an indirect positive effect on this indicator by reducing the early childbearing rate. Based on the research findings, several suggestions are made to improve household welfare; therefore, this paper can support the government in managing early childbearing rates and improving child well-being throughout the country.